Karakteristik Fisikokimia dan Penerimaan Konsumen Mayonnaise Rendah Lemak dengan Whey Protein (Shandong Kawah) sebagai Fat Replacer - Elisa Tri Nursari; Masrukan (Program Studi Teknologi Hasil Pertanian, 2026)
Increasing public awareness of healthy eating patterns has led to growing demand for low-fat food products with good sensory quality and nutritional value. Regular mayonnaise is high in fat and cholesterol because it uses oil and egg yolk as emulsifiers.Whey protein can emulsify and form gels, so it could replace egg yolk in low-fat mayonnaise.This study looked at how different amounts of whey protein affect the physicochemical properties, rheology, and consumer acceptance of mayonnaise. Low-fat mayonnaise was formulated with five concentrations of whey protein (0%, 2%, 4%, 6%, and 8%) using a Completely Randomized Design (CRD) with two replications. Parameters analyzed included moisture, fat, protein content, pH, viscosity, texture, color, emulsion stability, and hedonic tests. Results showed that increasing whey protein concentrations reduced fat content (from 37.68% to 29.87%) and increased protein content (from 2.86% to 5.08%). Viscosity increased substantially from 16.09 cP (control) to 38.99 cP at 8% whey protein, and emulsion stability improved from 87.10% (at 2% whey protein) to 100% at 8%, comparable to the control.High viscosity combined with a soft texture contributed to a more stable and sensorily preferred emulsion structure. The formulation with 4% whey protein provided the best balance of physical stability and consumer acceptance, achieving the highest overall hedonic score (3.17). Overall, this means whey protein can act as a functional alternative for developing healthier low-fat mayonnaise.